AIRLIFT BIOREACTOR FLUID-DYNAMIC CHARACTERIZATIONFOR THE CULTIVATION OF SHEAR STRESS SENSITIVEMICROORGANISMS - Rossi, M. J.; Nascimento, FX; Giachini, AJ; Oliveira, VL; Jr, A Furigo (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Airlift bioreactors are considered very efficient for aerobic cultivation of microorganisms. In particular, for the cultivation of filamentous fungi, where low shear rates may be required. In this context, the main aim of this study was to design an airlift bioreactor built with an external loop, adequate for biomass production of microbial organisms, including ectomycorrhizal fungi. A 5-L airlift bioreactor was constructed and experimental studies performed under an air-salt solution system (0.15 mol/L NaCl), in order to characterize the reactorÂ´s fluid-dynamic in relation to the superficial gas velocity (Ug) in the range of 0.001 to 0.020 m/s. In order to evaluate the performance of the reactor, a preliminary assay was conducted with the ectomycorrhizal fungus Rhizopogonnigrescens. Better gas separationreflected in better liquid circulation and higher oxygen transfer (0.0197 1/s at 1 vvm) when compared to an operating, 2.3-L prototype airlift. According to this study, volumetric coefficients for oxygen transfer (kLa) up to 0.020 1/s (specific airflow rates of 1.0 vvm) are sufficient to promote the growth of shear stress sensitive microorganisms, such as ectomycorrhizal fungi.